Tracking nuclear wave-packet dynamics in molecular oxygen ions with few-cycle infrared laser pulses - De, S.; Bocharova, I. A.; Magrakvelidze, Maia; Ray, D.; Cao, W.; Bergues, B.; Thumm, Uwe P. E.; Kling, Matthias F.; Litvinyuk, I. V.; Cocke, Charles L. (My University, 2013)
We have tracked nuclear wave-packet dynamics in doubly charged states of molecular oxygen using few-cycle infrared laser pulses. Bound and dissociating wave packets were launched and subsequently probed via a pair of 8-fs pulses of 790 nm radiation. Ionic fragments from the dissociating molecules were monitored by velocity-map imaging. Pronounced oscillations in the delay-dependent kinetic energy release spectra were observed. The occurrence of vibrational revivals permits us to identify the potential curves of the O[subscript 2] dication which are most relevant to the molecular dynamics. These studies show the accessibility to the dynamics of such higher-charged molecules.
Keywords: Nuclear-wave-packet dynamics; Molecular oxygen; Few-cycle infrared laser pulses